2021
DOI: 10.3389/fpsyg.2021.648401
|View full text |Cite
|
Sign up to set email alerts
|

Trait Emotional Intelligence and Wellbeing During the Pandemic: The Mediating Role of Meaning-Centered Coping

Abstract: Studies investigating the COVID-19 pandemic from a psychological point of view have mostly focused on psychological distress. This study adopts the framework of existential positive psychology, a second wave of positive psychology that emphasizes the importance of effective coping with the negative aspects of living in order to achieve greater wellbeing. Trait emotional intelligence (trait EI) can be crucial in this context as it refers to emotion-related personality dispositions concerning the understanding a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 88 publications
3
26
0
Order By: Relevance
“…It can be stated that the results are congruent with other studies conducted in Venezuela during the COVID-19 pandemic, specifically regarding adequate levels of academic self-efficacy (Romero et al, 2021); however, our results differ from that of the study conducted by Giménez and Medici (2021) regarding emotional intelligence skills. Our results are also congruent with international evidence suggesting that selfefficacy, emotional understanding, and regulation skills may be protective factors for mental health and well-being during a pandemic (Persich et al, 2021;Sabouripour et al, 2021;Sánchez-Ruiz et al, 2021); additionally, in this study, emotional perception established a proportional inverse relationship with psychological well-being, which is congruent with other studies before the pandemic (Extremera and Fernández-Berrocal, 2006;Extremera et al, 2009).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It can be stated that the results are congruent with other studies conducted in Venezuela during the COVID-19 pandemic, specifically regarding adequate levels of academic self-efficacy (Romero et al, 2021); however, our results differ from that of the study conducted by Giménez and Medici (2021) regarding emotional intelligence skills. Our results are also congruent with international evidence suggesting that selfefficacy, emotional understanding, and regulation skills may be protective factors for mental health and well-being during a pandemic (Persich et al, 2021;Sabouripour et al, 2021;Sánchez-Ruiz et al, 2021); additionally, in this study, emotional perception established a proportional inverse relationship with psychological well-being, which is congruent with other studies before the pandemic (Extremera and Fernández-Berrocal, 2006;Extremera et al, 2009).…”
Section: Discussionsupporting
confidence: 92%
“…It has aided in the development of resilience, well-being, and mental health in Spanish students during the COVID-19 pandemic ( Bartos et al, 2021 ). Specifically, emotional intelligence is a predictor of psychological well-being, enabling healthier coping strategies during COVID-19 pandemic by avoiding emotional distress ( Sánchez-Ruiz et al, 2021 ). Some experimental studies based on emotional intelligence and mindfulness in university students report a decrease in anxiety and depression symptoms during the confinement period ( Sturgill et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our results were consistent with previous findings. The maladaptive coping strategies was found to be correlated with the reduction in subjective well-being during the COVID-19 pandemic [ 67 , 68 , 69 ]. Previous literature suggested that those who reported higher levels of well-being tend to have less attachment to their smartphone, and experienced less fear of missing out [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are some studies on the relationship between EI and coping with stress in nurses and other health care professionals 6,20–23 and some in nursing students 20,24,25 . There are only a few studies which address EI and stress in nurses during the COVID‐19 pandemic 26–28 . Thus, we wanted to examine how EI influences ICU nurses and their coping strategies, and this study aimed to assess the level of EI, coping strategies, and the relationship between these variables among adult ICU nurses in Poland.…”
Section: Introductionmentioning
confidence: 99%
“…20,24,25 There are only a few studies which address EI and stress in nurses during the COVID-19 pandemic. [26][27][28] Thus, we wanted to examine how EI influences ICU nurses and their coping strategies, and this study aimed to assess the level of EI, coping strategies, and the relationship between these variables among adult ICU nurses in Poland.…”
mentioning
confidence: 99%